2022
DOI: 10.1088/1361-6501/ac82dd
|View full text |Cite
|
Sign up to set email alerts
|

Centimeter-level positioning by instantaneous lidar-aided GNSS ambiguity resolution

Abstract: High-precision vehicle positioning is key to the implementation of modern driving systems in urban environments. Global Navigation Satellite System (GNSS) carrier phase measurements can provide millimeter- to centimeter-level positioning, provided that the integer ambiguities are correctly resolved. Abundant code measurements are often used to facilitate integer ambiguity resolution (IAR), however, they suffer from signal blockage and multipath in urban canyons. In this contribution, a lidar-aided instantaneou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 40 publications
0
0
0
Order By: Relevance
“…Second, it has been utilised to enable integer ambiguity resolution in RTK. For instance, a lidar-aided instantaneous ambiguity resolution method was presented in (Zhang et al, 2022) which achieved the ambiguity success rate of 100% using single-system single-frequency observations. Finally, numerous studies have shown the effectiveness of lidar measurements for speeding up the convergence of PPP by successive scan matching (Li et al, 2021a, Li et al, 2021b, Li et al, 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Second, it has been utilised to enable integer ambiguity resolution in RTK. For instance, a lidar-aided instantaneous ambiguity resolution method was presented in (Zhang et al, 2022) which achieved the ambiguity success rate of 100% using single-system single-frequency observations. Finally, numerous studies have shown the effectiveness of lidar measurements for speeding up the convergence of PPP by successive scan matching (Li et al, 2021a, Li et al, 2021b, Li et al, 2022.…”
Section: Introductionmentioning
confidence: 99%